Electronic case studies: a problem-based learning approach to management development. (26th June 2007) - Drinkwater, Philip M.; Holland, Christopher P.; Papamichail, Konstantinia Nadia
Electronic case studies (e-Cases) are hypertext documents that focus on a single company or business theme. An e-Case differs from a traditional case study in that it is a dynamic account of a business situation. The hypertext links point to data that are automatically updated, such as company websites and secondary data in areas such as financial accounts or market overviews. The approach encourages participants to develop problem-based strategies centred on the concept of jigsaw learning. A range of e-Case examples has been developed and this paper serves as a note for instructors on how best to use them.